2005
DOI: 10.1158/0008-5472.can-04-4426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Hypoxia-Inducible Factor-1α as a Cancer Therapeutic Target via Inducible RNA Interference In vivo

Abstract: Validating potential targets is an important step in the drug discovery process. In this study, we tested the feasibility of using inducible RNA interference (RNAi) in vivo to obtain an unbiased evaluation on the efficacy of inhibiting hypoxiainducible factor-1A (HIF-1A) in established tumors. We showed that HIF-1A inhibition resulted in transient tumor stasis or tumor regression, and inhibiting HIF-1A in earlystage tumors was found to be more efficacious than inhibiting HIF-1A in more established tumors. A di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 24 publications
9
68
0
Order By: Relevance
“…7 Similarly, it has been previously reported that hypoxia and HIF-1a lead to the development of osteolytic lesions and tumor growth in breast cancer in vivo models. 26 In conclusion, as in other tumoral models where it has been shown that HIF-1a inhibition exerts a potent in vivo antitumor effect, including the squamous cell carcinoma, liver and lung cancer, 48,49 our data indicate that selective HIF-1a inhibition results in a potent anti-MM effect by blocking angiogenesis and the development of osteolytic bone lesions. These results suggest that HIF-1a is a potential therapeutic target in MM.…”
Section: Discussionsupporting
confidence: 77%
“…7 Similarly, it has been previously reported that hypoxia and HIF-1a lead to the development of osteolytic lesions and tumor growth in breast cancer in vivo models. 26 In conclusion, as in other tumoral models where it has been shown that HIF-1a inhibition exerts a potent in vivo antitumor effect, including the squamous cell carcinoma, liver and lung cancer, 48,49 our data indicate that selective HIF-1a inhibition results in a potent anti-MM effect by blocking angiogenesis and the development of osteolytic bone lesions. These results suggest that HIF-1a is a potential therapeutic target in MM.…”
Section: Discussionsupporting
confidence: 77%
“…The pharmacologic validation of HIF-1 as a therapeutic target has not been fully elucidated because of the lack of selective inhibitors (6). The potential outcome of HIF-1 inhibition in cancer therapy is promising, based on genetic approaches and preclinical models (1,6), and the shRNA targeting of HIF-1α was shown to inhibit tumor growth (33,34). In this study, we provide further evidence that disruption of the HIF-1 pathway by targeting its upstream activator SEPT9_i1 with shRNA is effective for tumor growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…However, the roles HIF-1a plays in hypoxiarelated drug resistance are still inconclusive. 6,10,[30][31][32][33] Moreover, how HIF-1 cooperates with p53 to determine drug sensitivity remains poorly known. Inhibition of glucose transport-1 expression and also drug resistancerelated proteins such as mdr1, mrp and lrp, and increased level of proapoptotic proteins such as Bid and Bax were ever reported to form the therapeutic basis of HIF-1 interference.…”
Section: Discussionmentioning
confidence: 99%